Black Panther panther's rage - McGregor, Don 1945-; Lee, Stan 1922-2018 (Marvel Worldwide, Inc., 2016)
"In the 1960s, Stan Lee and Jack Kirby created an unprecedented string of classic comic book heroes. Quite possibly the most iconic of them all was the high-tech king of Wakanda, The Black Panther. When the Panther began his own solo series, Don McGregor strove to meet Lee and Kirby's high standard with "Panther's Rage." It was an epic adventure so huge it ranged across the savannah, into the deepest jungles and up snow-topped mountains. Over its course, McGregor would explore and expand the life and culture of Wakandans and their African kingdom in compelling detail. Then, in a challenging storyline, he sent the Black Panther to the American South to seek justice for a murder connected to the Klan and the Soul Strangler"--Back cover
Fantastic Four #52-53 and Jungle action #6-24 --
Keywords: Black Panther / (Fictitious character) / Comic books, strips, etc; Black Panther / (Fictitious character); Superheroes / Comic books, strips, etc; Good and evil / Comic books, strips, etc; Blacks / Comic books, strips, etc; Supervillains / Comic books, strips, etc; Revenge / Comic books, strips, etc; Heroes / Africa / Comic books, strips, etc; Africa / Comic books, strips, etc; Blacks; Good and evil; Heroes; Revenge; Superheroes; Supervillains; Africa; Graphic novels; Comics (Graphic works); Superhero comics; Science fiction comics; Comics (Graphic works) / United States; Comic books, strips, etc; Comic